KONGSI PEMILIKAN RUMAH BERBASIS SYARIAH PERBANDINGAN ANTARA BANK MUAMALAT INDONESIA DAN BANK RAKYAT INDONESIA SYARIAH - RIZAL RIZAL; ELFADHLI ELFADHLI; FATIMAH SETIA WARDHANI; ZAINUDDIN ZAINUDDIN (Maqdis: Jurnal Kajian Ekonomi Islam, 2018)
The purpose of this study was to explain the comparison of financing processes, asset acquisition, and transfer of home ownership financing with Musyarakah Mutanaqisah and Ijarah muntahiyah Bitamlik. The research object was at Bank Muamalat Indonesia, Solok Branch Office and at Bank Rakyat Indonesia Syariah Padang Branch. The type of research used is qualitative comparative research. The data collection technique used is through interviews and documentation. Data processing is done by qualitative comparative analysis techniques. The results of the study are: First, the process of financing home ownership with musyarakah mutanaqisah is longer than ijarah muntahiyah bitamlik. Second, the procurement of assets with musyrakah mutanaqisah is clearer than ijarah muntahiyah bitamlik. Third, the transfer of ownership in the financing of home ownership with Musyarakah Mutanaqisah process is certain, while the transfer of home ownership with Ijarah Muntahiyah Bitamlik the process is uncertain. Fourth, financing using the Musharaka Mutanaqisah agreement is superior to the Ijarah muntahiya bitamlik both in terms of procurement, certainty of ownership transfer and in terms of legality to collateral. Although in terms of the process it is faster on Ijarah Muntahiya Bittamlik.